PENGARUH BRAND TRUST, CUSTOMER SATISFACTION, DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP BRAND LOYALTY - Rini, Ayu Stia; Sulistyawati, Eka (E-Jurnal Manajemen, 2014)
Aqua is a brand of Bottled Drinking Water (bottled water) which became one of the favorites in Indonesia. Brand loyalty is a positive attitude in making purchases over to a brand over time despite situational influences and marketing efforts have the potential to lead to brand switching. There are several variables that affect brand loyalty, such as brand trust, customer satisfaction, and Corporate Social Responsibility (CSR). This study aimed to determine the influence of brand trust, customer satisfaction, and brand loyalty on CSR to Aqua in Denpasar City. The sample used there are 120 respondents with purposive sampling method. The data analysis technique used is multiple linear regression analysis techniques. Based on the results of analysis show that partially brand trust and CSR are positive effect and significant on brand loyalty. As for the customer satisfaction is positive effect and not significant on brand loyalty.
Keywords: brand trust, customer satisfaction, CSR, brand loyalty, aqua